COMPARISON OF STUDENT’S SELF-ASSESSMENT TO EXAMINERS ASSESSMENT IN A FORMATIVE OBSERVED STRUCTURAL CLINICAL EXAMINATION (OSCE) AND CORRELATION BETWEEN CUMULATIVE SCORE AND GLOBAL RATING SCALE FOR STUDENTS AND EXAMINERS EVALUATION - Jahan, Firdous; Shaikh, Naeem; Norrish, Mark; Siddqi, Najam; Qasim, Rizwan (Journal of Postgraduate Medical Institute, 2012)
Objective: To compare students' self-assessment with assessment by examiners in a formative observed structured clinical examination (OSCE) and comparison between cumulative score and global rating scale for students and faculty evaluation. Methodology: This cross sectional study was carried out on 6th year medical students of Oman Medical College, Family Medicine rotation in a formative OSCE. A self-assessment questionnaire was completed by 15, Year 6 students immediately after the OSCE. Statistical analysis was done with SPSS 16.0 for Windows. Regression analysis was used to correlate self reported rating and actual performance in each station. A p value of < 0.05 was considered significant. Correlation between cumulative score and global rating scale for students and faculty evaluation was calculated by Pearson correlation. Results: Students has done appropriate self-assessment on dyspepsia history while the other two stations have shown some discrepancies in self-assessment and examiners assessment. Conclusion: Self-assessment is comparable to examiner evaluation. Examiners assessment has shown consistent and positive correlation between cumulative scores and global rating scores while students had failed to show this consistency.